The effect of aging processes on tribo-metallurgy properties of al based ternary alloys product by P/M technique - Kaplan, Yavuz; Aksöz, Sinan; Ada, H.; İnce, E.; Özsoy, S. (National Library of Serbia, 2020)
In this study, Al matrix composites consisting of different amounts of Zn, Cu, and Mg were produced using the powder metallurgy technique. In the alloying, powders were ball milled for 120 min via mechanical alloying. After alloying process, the powders were pressed at 800 MPa at room temperature. Sintering (2 h at 600?C in argon atmosphere), solution treatment (2 h at 480?C), and aging processes (3, 6, 9, and 12 h, respectively, at 120?C) were applied to the samples. The hardness and tribo-metallurgy properties of the products were investigated. After sintering, the hardness values of the three alloys were close to each other; however, the solution treatment after sintering caused the hardness values to increase significantly. It was determined that the Al-2Zn-5Cu-4Mg alloy had the highest hardness increase with the 6-h aging heat treatment. The wear resistance of the materials in all the compositions had increased. The highest wear resistance and lowest friction coefficient were obtained for the Al-2Zn-5Cu-4Mg alloy with the 6-h aging heat treatment.
Keywords: Aging; wear; sintering; Tribology; Ternary Alloys, Tribology; Chemical technology; aging; ternary alloys; Ternary Alloys; TP1-1185; Sintering; Wear; tribology